2020
DOI: 10.4048/jbc.2020.23.e30
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Event Analysis in Breast Cancer Patients Who Received Breast-Conserving Surgery and Post-Operative Radiotherapy: a Korean Nationwide Cohort Study

Abstract: Purpose: Adjuvant breast radiotherapy (RT) following breast-conserving surgery (BCS) has been reported to induce cardiac toxicity in breast cancer patients. We investigated the incidence and risk factors of major coronary events after breast RT using Korean nationwide Health Insurance Review and Assessment data. Methods: Using data from a nationwide quality assessment of breast cancer treatment, we identified 3,251 patients who received breast RT after BCS in 2013. Data about major coronary events were additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
3
0
4
Order By: Relevance
“…Al fine di minimizzare il rischio di CAD, per quanto non si possa definire una dose soglia, è consigliato mantenere la dose media cardiaca al di sotto dei 5 Gy, la V25Gy del cuore inferiore al 5% e la dose alla regione coronarica al di sotto di 20 Gy in frazionamento convenzionale. In relazione alla più recente introduzione di schedule di trattamento ipofrazionato, vi sono pochi dati dosimetrici definitivi che possano essere utilizzati come riferimenti certi; si consiglia pertanto l'utilizzo di dosi-soglia biologicamente equivalenti a quelle sopra riportate 91,[94][95][96][97][98][99][100] .…”
Section: (A) Aspetti Generali E Fattori DI Rischiounclassified
See 1 more Smart Citation
“…Al fine di minimizzare il rischio di CAD, per quanto non si possa definire una dose soglia, è consigliato mantenere la dose media cardiaca al di sotto dei 5 Gy, la V25Gy del cuore inferiore al 5% e la dose alla regione coronarica al di sotto di 20 Gy in frazionamento convenzionale. In relazione alla più recente introduzione di schedule di trattamento ipofrazionato, vi sono pochi dati dosimetrici definitivi che possano essere utilizzati come riferimenti certi; si consiglia pertanto l'utilizzo di dosi-soglia biologicamente equivalenti a quelle sopra riportate 91,[94][95][96][97][98][99][100] .…”
Section: (A) Aspetti Generali E Fattori DI Rischiounclassified
“…Infine una recente metanalisi 91 ha confermato come l'omissione della radioterapia in pazienti di età ⩾70 anni con neoplasie in stadio iniziale, sottoposte a terapia con tamoxifene, comporti uno svantaggio in termini di recidiva locale e locoregionale, ma non in termini di sopravvivenza globale. In conclusione, in base ai dati attualmente disponibili in letteratura [89][90][91][92][93][94][95][96][97][98][99][100] , è possibile che l'integrazione di specifici fattori prognostici associati alle pazienti e alla neoplasia possano consentire di individuare una classe di pazienti a basso rischio nelle quali omettere la radioterapia adiuvante 101,102 .…”
Section: Quesito Clinico Nunclassified
“…Therefore, long-term observation is needed [ 2 , 3 ]. Third, pre-existing risk factors such as smoking, old age, obesity, cardio-metabolic risk factors of hypertension and diabetes, and other cardiovascular or cerebrovascular disease can affect cardiac toxicity [ 4 6 ]. Most importantly, cardiac toxicity increases gradually per mean heart dose without a clear threshold [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a 5.3% rate of major coronary events (MACE) after RT in breast cancer patients. Moreover, patients with high blood pressure, diabetes mellitus, and cerebrovascular accidents had 3-year coronary event-free survival rates that were inferior to those of the patients without such comorbidities [ 4 ] The increase in the rate of MACE was proportional to the radiation dose; MACE manifested within up to at least 20 years [ 5 ].…”
mentioning
confidence: 99%
“…A meta-analysis showed that significant cardiovascular mortality after RT of the left breast, compared with that of the right breast, was more obvious after a long follow-up of over 15 years [ 6 ]. Thus, in breast cancer patients with cardiovascular risk factors, RT should include heart-sparing methods, or it may be performed via intensity-modulated technology to avoid significant cardiotoxicity [ 4 ].…”
mentioning
confidence: 99%